Pelatihan Da’i Antikorupsi bagi Mubaligh-Mubalighah Terdampak Physical Distancing Akibat Pandemi Covid-19 di Kelurahan Prenggan, Kotagede, Yogyakarta - Suyadi Suyadi; Waharjani Waharjani; Sumaryati Sumaryati; Trisna Sukmayadi (Universitas Mathla'ul Anwar Banten, 2020)
ANTI-CORRUPTION DA'I TRAINING FOR MUBALIGH-MUBALIGHAH AFFECTED BY PHYSICAL DISTANCING DUE TO THE COVID-19 PANDEMIC IN PRENGGAN VILLAGE, KOTAGEDE, YOGYAKARTA. Prenggan, Kotagede, Yogyakarta is one of the villages which is chosen to be the pilot project for anti-corruption by the Corruption Eradication Committee. This village is affected by physical distancing due to the Covid-19 pandemic. It implies to all components of the village that contribute to building the image of Prenggan as an anti-corruption village. One of the elements of the village is the mosque with its Mubaligh (preacher). However, during the pandemic, they contribute the smallest to establish the anti-corruption image. Therefore, they should learn to use online media to spread Islamic teachings in relation to anti corruption. The community service takes the form of online training that includes socialization, counseling, practice, and evaluation or monitoring. The application used in the program is Google Meet and WhatsApp Group. The results show that online training improves the anti-corruption competence of the Da’is and Mubalighs in Prenggan village. The improvement includes three aspects: the understanding of the fiqh (jurisprudence) of anti-corruption, the da’wah rhetoric for anti-corruption, and the skills to utilize the advance of information technology, especially Google Meet.